Ureteral inflammatory edema grading clinical application - Li, Jialin; Jiang, Chengming; Liao, Xinzhi; Yan, Sheng; Huang, Sigen; Liu, Shengyin; Liu, Quanliang (Frontiers in Surgery, 2023)
Purpose: To evaluate the relationship between endoscopic Ureteral inflammatory edema and ureteral lumen, formulate a preliminary grading method for the severity of Ureteral inflammatory edema, and analyze the impact of Ureteral inflammatory edema under different grading on endoscopic ureteral calculi surgery and prognosis. Materials and Methods: We retrospectively analyzed 185 patients between January 2021 and November 2021 to evaluate the grading of Ureteral inflammatory edema by endoscopic observation of Ureteral inflammatory edema and lumen conditions. Also, the factors influencing between Ureteral inflammatory edema grading and URS and on patient prognosis were analyzed based on multiple linear regression and binary logistic regression, with appropriate postoperative management measures proposed. Results: A total of 185 patients fulfilled the criteria and were included in this study for evaluation of Ureteral inflammatory edema. We performed a statistical analysis of the collected patient information, excluding confounding factors, and found that Ureteral inflammatory edema grade was significantly correlated with patient age, hydronephrosis grade, ureteroscope placement time, operative time, intraoperative bleeding, and indicators of postoperative ureteral stricture (P<0.05). logistics regression analysis showed that intraoperative ureteroscope placement time and Surgery time gradually increased with Ureteral inflammatory edema grade prolonged, and Ureteral inflammatory edema grading was negatively correlated with the improvement of postoperative hydronephrosis and the appearance of postoperative ureteral stenosis, and intraoperative bleeding was significantly increased at Ureteral inflammatory edema grading of grade 3. Conclusions: Ureteral inflammatory edema grading can be used as an adjunctive clinical guide for endoscopic treatment of upper urinary tract stones.